Prophylactic effect of herbal-marine compound (HESA-A) on influenza A virus infectivity - Mehrbod, Parvaneh; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair (BioMed Central, 2014)
BACKGROUND: Influenza virus is still a severe respiratory disease affecting human and other species. As conventional drugs are not recommended for long time because of side effects and drug resistance occurrence, traditional medication has been focused as alternative remedy. HESA-A is a natural compound from herbal-marine origin. Previous studies have reported the therapeutic properties of HESA-A on psoriasis vulgaris and different types of cancers and we also showed its anti-inflammatory effects against influenza A infection. METHODS: This study was designed to investigate the potential properties of HESA-A as prophylaxis or treatment. To investigate the prophylaxis or treatment activities of HESA-A, Madin-Darby Canine Kidney (MDCK) cells were exposed to HESA-A and influenza A virus in different manners of exposure and different time intervals. The results were evaluated by MTT and HA assays. RESULTS: It was found that HESA-A is much more effective against influenza cytopathic effects when it is applied for prophylaxis and also in concurrent treatment (p ≤ 0.05) but not in post-infection treatment (p ≥ 0.05). CONCLUSION: In conclusion, HESA-A is significantly effective against influenza replication in prophylaxis application affecting the virus penetration/adsorption to the cell without any toxic effect on the cell viability.